Neurofeedback for attention-deficit/hyperactivity disorder: meta-Analysis of clinical and neuropsychological outcomes from randomized controlled trials - Cortese, Samuel; Ferrin, Maite; Brandeis, Daniel; Holtmann, Martin; Aggensteiner, Pascal; Daley, David; Santosh, Paramala; Simonoff, Emily; Stevenson, Jim; Stringaris, Argyris; Sonuga-Barke, Edmund J.S. (Elsevier, 2016)
Objective: We performed meta-analyses of randomized controlled trials to examine the effects of neurofeedback on attention-deficit/hyperactivity disorder (ADHD) symptoms and neuropsychological deficits in children and adolescents with ADHD.